Pengembangan Model Senam DIGIFUN untuk Meningkatkan Partisipasi Gerak Siswa Sekolah Dasar - Karlina Dwijayanti; Arif Rohman Hakim; Fata Laila Fatkhur Rahman (MAN Insan Cendekia Jambi, 2026)
Physical activity participation among elementary school students in Physical Education, Sports, and Health (PJOK) classes remains low due to the use of conventional and unengaging teaching methods. This study was designed to develop and test the effectiveness of the DIGIFUN Gymnastics model a digital-based learning innovation utilizing a